Improving Junior High Schools’ Critical Thinking Skills Based on Test Three Different Models of Learning - Fuad, Nur Miftahul; Zubaidah, Siti; Mahanal, Susriyati; Suarsini, Endang (International Journal of Instruction, 2017)
The aims of this study were (1) to find out the differences in critical thinking skills among students who were given three different learning models: differentiated science inquiry combined with mind map, differentiated science inquiry model, and conventional model, (2) to find out the differences of critical thinking skills among male and female students. This study is a quasi-experimental research with pretest-posttest nonequivalent control group design. The population in this research is the seventh grade students of junior high schools in Kediri, Indonesia. The sample of the research is in the number of 96 students distributed in three classes at different schools. The data of critical thinking skills are gained from test scores and then analyzed using descriptive and inferential statistics through ANCOVA. The results of research revealed that there are different skills in critical thinking in different models. The highest skills in critical thinking are reached by students who were given differentiated science inquiry model combined with mind map in their learning. There are also differences in critical thinking skills between male and female students.